Allostatic load, a measure of cumulative physiological stress, impairs brain structure but not β-accumulation in older adults: an exploratory study - Palix, Cassandre; Chauveau, Léa; Felisatti, Francesca; Chocat, Anne; Coulbault, Laurent; Hébert, Oriane; Mézenge, Florence; Landeau, Brigitte; Haudry, Sacha; Fauvel, Séverine; Collette, Fabienne; Klimecki, Olga; et al. (Frontiers in Aging Neuroscience, 2025)
IntroductionAllostatic load (AL) is a composite score of progressive physiological dysregulations in response to long-term exposure to everyday stress. Despite growing interest, limited research has focused on links with cerebral and cognitive aspects of aging and with markers sensitive to Alzheimer’s disease (AD) in a healthy elderly population and with a multimodal approach.MethodsAt baseline, 111 older adults (without cognitive impairment) from the Age-Well trial completed blood and anthropometric markers collection, cognitive assessments and multimodal neuroimaging within 3 months.ResultsAL was negatively associated with gray matter volume and white matter integrity within frontal and temporal regions and poorer attentional performance.DiscussionAL is linked to structural brain integrity in aging- and stress-sensitive regions but not with AD-related markers (β-amyloid load) and only in two AD-sensitive brain regions in older adults. These results highlight the potential interest of AL as a sensitive index of stress-induced brain aging.